2021
DOI: 10.1371/journal.pmed.1003856
|View full text |Cite
|
Sign up to set email alerts
|

Adverse pregnancy outcomes in women with diabetes-related microvascular disease and risks of disease progression in pregnancy: A systematic review and meta-analysis

Abstract: Background The rise in the global prevalence of diabetes, particularly among younger people, has led to an increase in the number of pregnant women with preexisting diabetes, many of whom have diabetes-related microvascular complications. We aimed to estimate the magnitude of the risks of adverse pregnancy outcomes or disease progression in this population. Methods and findings We undertook a systematic review and meta-analysis on maternal and perinatal complications in women with type 1 or 2 diabetic microv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 62 publications
(156 reference statements)
0
15
0
Order By: Relevance
“…DR was associated with any preterm birth and preeclampsia. The risks of onset or worsening of DR were increased in women who were nulliparous, smokers, presented with existing proliferative disease, had more chronic diabetes [ 20 ]. Our results also show that hypertension, renal failure, eclampsia, caesarean section, and induced labor are general risk factors for DR.…”
Section: Discussionmentioning
confidence: 99%
“…DR was associated with any preterm birth and preeclampsia. The risks of onset or worsening of DR were increased in women who were nulliparous, smokers, presented with existing proliferative disease, had more chronic diabetes [ 20 ]. Our results also show that hypertension, renal failure, eclampsia, caesarean section, and induced labor are general risk factors for DR.…”
Section: Discussionmentioning
confidence: 99%
“…GDM has been demonstrated to be closely associated with considerable maternal and neonatal short-term and long-term complications. 5 7 9 11 The traditional mode of GDM management is effective but requires intensive clinical input. 15 18 In recent years, web-based interventions have become increasingly popular in the field of GDM management due to making treatments more accessible and affordable.…”
Section: Discussionmentioning
confidence: 99%
“…GDM has been demonstrated to be closely associated with considerable maternal and neonatal short-term and long-term complications 5 7 9 11. The traditional mode of GDM management is effective but requires intensive clinical input 15 18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined effects of higher maternal age and higher parity on overweight and obesity could explain the high prevalence of hypertension and diabetes among grand multipara [ 1 , 4 ]. The literature from many countries, including the UAE, revealed that chronic diseases (e.g., diabetes mellitus) are associated with adverse pregnancy outcomes [ 23 , 24 ]. For example, a systematic review and meta-analysis conducted by Relph et al showed mothers with uncontrolled diabetes mellitus were at greater risk of preeclampsia, preterm birth, perinatal death, congenital abnormality, small for gestational age, and admissions to NICU [ 23 ].…”
Section: Discussionmentioning
confidence: 99%